Face-to-Face Teaching Skills of Virtually Mentored Pre-Service Interns - Molina, Karen Joy; Baligod, Janella; Licupa, Loverlen; Auayang, Kristine Mae; Bangi, Jennifer (Journal of Interdisciplinary Perspectives, 2024)
During the COVID-19 pandemic, pre-service teachers found completing their online teaching practicum impossible. Their doubt extended to their thoughts about making it difficult for them to perform their obligations effectively as practicing teachers. This basic qualitative research aimed to explore the practices and experiences of graduates in their online teaching internships and their effect on their teaching experience. Fifteen Teacher Education alumni participated in this study and were selected through purposive sampling. Data was collected using semi-structured interview questions and gathered through Google Meet and face-to-face interviews. Thematic data analysis was used to identify essential themes. Based on the results and discussion of the study, Teacher Education graduates of a Catholic Institution were exposed to unforgettable experiences and practices with their supervising instructor, cooperating teacher, school culture, and peers, which they continue to utilize in their current teaching roles. Subsequently, the study revealed that their experiences led them to the following: (a) commitment to the ongoing development of soft skills, (b) enhanced technological skills, (c) strengthened cooperation among coworkers and supervisors, (d) improved classroom management strategies, (e) innovation of assessment strategies, (f) refined creativity in creating instructional resources and (g) improved sense of accountability and adaptability. This implies that the online environment did not deter the would-be teachers from developing the skills necessary in the contemporary world. Thus, this study recommends enhancing the implementation of hybrid teaching internships in the teacher-education program.